Modulating cardiac physiology in engineered heart tissue with the bidirectional optogenetic tool BiPOLES - Schwarzová, Barbora; Stüdemann, Tim; Sönmez, Muhammed; Rössinger, Judith; Pan, Bangfen; Eschenhagen, Thomas; Stenzig, Justus; Wiegert, Simon; Christ, Torsten; Weinberger, Florian (Pflügers Archiv, 2023)
Optogenetic actuators are rapidly advancing tools used to control physiology in excitable cells, such as neurons and cardiomyocytes. In neuroscience, these tools have been used to either excite or inhibit neuronal activity. Cell type-targeted actuators have allowed to study the function of distinct cell populations. Whereas the first described cation channelrhodopsins allowed to excite specific neuronal cell populations, anion channelrhodopsins were used to inhibit neuronal activity. To allow for simultaneous excitation and inhibition, opsin combinations with low spectral overlap were introduced. BiPOLES (Bidirectional Pair of Opsins for Light-induced Excitation and Silencing) is a bidirectional optogenetic tool consisting of the anion channel Guillardia theta anion-conducting channelrhodopsin 2 (GtACR2 with a blue excitation spectrum and the red-shifted cation channel Chrimson. Here, we studied the effects of BiPOLES activation in cardiomyocytes. For this, we knocked in BiPOLES into the adeno-associated virus integration site 1 (AAVS1) locus of human-induced pluripotent stem cells (hiPSC), subjected these to cardiac differentiation, and generated BiPOLES expressing engineered heart tissue (EHT) for physiological characterization. Continuous light application activating either GtACR2 or Chrimson resulted in cardiomyocyte depolarization and thus stopped EHT contractility. In contrast, short light pulses, with red as well as with blue light, triggered action potentials (AP) up to a rate of 240 bpm. In summary, we demonstrate that cation, as well as anion channelrhodopsins, can be used to activate stem cell-derived cardiomyocytes with pulsed photostimulation but also to silence cardiac contractility with prolonged photostimulation.
Gesehen am 30.01.2024